العمارة القديمة في سوريا: جنوب حوران : [Ancient Architecture in Syria: Southern Hauran] - Butler, Howard Crosby (BRILL, 2021)
The Ancient Architecture in Syria (Southern Hauran) , written by Howard C. Butler and translated by Aisha Moussa, is the product of studying 65 ancient sites in Southern Hauran. It focuses on the archeological and architectural heritage and presents detailed drawings of plans; restoration of buildings; and photographs of monuments, inscriptions and sculptures. The book covers the late pre-historic, Nabataean, Roman, Christian, and early Islamic periods (1st century B.C.E.- 7th century C.E.). Many of the monuments described by Butler have long since disappeared or been destroyed, so this book provides an invaluable, thorough, detailed, and photographic documentation of the archeological treasure in Syria, the cradle of civilizations, particularly in view of the current pressing need for development and investment there. يعد كتاب العمارة القديمة في سوريا (جنوب حوران) ، من تأليف هوارد كروسبي باتلر وترجمة عائشة موسى، ثمرة دراسة 56 موقعًا أثريًا قديمًا في جنوب حوران. ويتناول الكتاب دراسة تراث الفن الأثري والمعماري ويعرض رسمًا مفصلًا للمخططات وترميمًا للمباني وتصويرًا للصروح الأثرية والنقوش والمنحوتات. كما يغطي الكتاب أواخر عصور ما قبل التاريخ والفترة النبطية والرومانية والمسيحية ومطلع الحقبة الإسلامية، في فترة تمتد بين القرن الأول قبل الميلاد ومطلع القرن السابع الميلادي. لقد اختفت العديد من المعالم الأثرية التي صورها باتلر منذ أمد بعيد أو دمرت، لذلك يقدم هذا الكتاب توثيقًا مصورًا لا يقدر بثمن ويعد الأكثر شمولًا ودقة عن الكنوز الأثرية الثمينة في سوريا مهد الحضارات، لا سيما في ظل الحاجة الملحّة الآن لتنشيط مشاريع التنمية وخلق فرص الاستثمار فيها.